HIV DALAM KEHAMILAN - Helwinofira Helwinofira; Soufni Morawati (Yayasan Nusantara Hasana Berdikari, 2026)
Human Immunodeficiency Virus Infection in pregnancy is a global health problem that may increase morbidity and mortality risks for both mother and infant. Mother-to-child transmission of HIV can occur during pregnancy, delivery, or breastfeeding. Risk factors influencing transmission include high maternal viral load, lack of antiretroviral therapy, opportunistic infections, and certain obstetric conditions. Clinical manifestations in pregnant women with HIV vary from asymptomatic conditions to severe opportunistic infections due to immune system suppression. Diagnosis is established through serological testing and viral load examination to assess the severity of infection. Management of HIV in pregnancy focuses on optimal antiretroviral therapy, monitoring maternal and fetal conditions, and preventing vertical transmission. With early detection and adequate therapy, the risk of mother-to-child HIV transmission can be significantly reduced, thereby improving the quality of life of both mother and child.